CPD in the built environment - Watts, Greg (Gregory N.); Watts, Norman ([Place of publication not identified] : Routledge, 2021)
The aim of this book is to provide a single source of information to support continuing professional development (CPD) in the built environment sector. The book offers a comprehensive introduction to the concept of CPD and provides robust guidance on the methods and benefits of identifying, planning, monitoring, actioning, and recording CPD activities. It brings together theories, standards, professional and industry requirements, and contemporary arguments around individual personal and professional development. Practical techniques and real-life best practice examples outlined from within and outside of the industry empower the reader to take control of their own built environment-related development, whilst also providing information on how to develop fellow staff members. The contents covered in this book align with the requirements of numerous professional bodies, such as the Royal Institution of Chartered Surveyors (RICS), the Institution of Civil Engineers(ICE), and the Chartered Institute of Builders (CIOB). The chapters are supported by case studies, templates, practical advice, and guidance. The book is designed to help all current and future built environment professionals manage their own CPD as well as managing the CPD of others. This includes helping undergraduate and postgraduate students complete CPD requirements for modules as part of a wide range of built environment university degree courses and current built environment professionals of all levels and disciplines who wish to enhance their careers through personal and professional development, whether due to professional body requirements or by taking control of identifying and achieving their own educational needs.
1. What is Continuous Professional Development 2. The Construction Industry and CPD 3. Professional Bodies in the Construction Industry 4. Goal Setting 5. Goal Planning 6. Reflecting on CPD 7. Organisations and CPD 8. Managing the CPD of others 9. Why Construction Professionals Need to Take Responsibility for their own Career Development
OCLC-licensed vendor bibliographic record.
Keywords: Building -- Study and teaching; Building -- Vocational guidance; Continuing education; SELF-HELP / Personal Growth / General